Effect of β-defensin 2 on biofilm formation in pathogenic E. coli bacteria isolated from clinical samples (Texas Journal of Agriculture and Biological Sciences, 2022)
Biofilms are formed by bacteria as part of their survival processes, and they are so common in nature. Biofilms are made up of microbial communities that are encased in a layer of self-produced extracellular polymers. Biofilms form on both abiotic and biotic surfaces and are important in a variety of settings, including aquaculture, the food industry, and the clinical field as a factor in antimicrobial drug resistance. Several studies on the mechanisms of interaction between defensins and cell membranes have revealed that positively charged defensin residues interact with negatively charged components (lipopolysaccharides or phospholipids) in microbial membranes to disrupt the cell membrane as the first step in killing bacteria. The goal of this study is to demonstrate the effect of beta-defensin 2 on biofilm formation by E. coli. To examine the biofilm formation of 67 E. coli isolates, microtiter plate method was used. After that, the mic of beta-defensin 2 was determined, then an anti-biofilm test was conducted to find out the extent of its effect on biofilm formation. The results of examining the ability of bacteria to produce biofilm showed that all isolates were biofilm producers in varying degrees. β-defensin 2 was shown to be effective in eliminating biofilms formed by E. coli.